Efficient hydrogen storage in up-scale metal hydride tanks as possible metal hydride compression agents equipped with aluminium extended surfaces - Gkanas, Evangelos I.; Grant, David M.; Khzouz, Martin; Stuart, Alastair D.; Manickam, Kandavel; Walker, Gavin S. (Elsevier, 2016)
In the current work, a three-dimensional computational study regarding coupled heat and mass transfer during both the hydrogenation and dehydrogenation process in upscale cylindrical metal hydride reactors is presented, analysed and optimized. Three different heat management scenarios were examined at the degree to which they provide improved system performance. The three scenarios were: 1) plain embedded cooling/heating tubes, 2) transverse finned tubes and 3) longitudinal finned tubes. A detailed optimization study was presented leading to the selection of the optimized geometries. In addition, two different types of hydrides, LaNi5 and an AB2-type intermetallic were studied as possible candidate materials for using as the first stage alloys in a two-stage metal hydride hydrogen compression system. As extracted from the above results, it is clear that the case of using a vessel equipped with 16 longitudinal finned tubes is the most efficient way to enhance the hydrogenation kinetics when using both LaNi5 and the AB2-alloy as the hydride agents. When using LaNi5 as the operating hydride the case of the vessel equipped with 60 embedded cooling tubes presents the same kinetic behaviour with the case of the vessel equipped with 12 longitudinal finned tubes, so in that way, by using extended surfaces to enhance the heat exchange can reduce the total number of tubes from 60 to 12. For the case of using the AB2-type material as the operating hydride the performance of the extended surfaces is more dominant and effective compared to the case of using the embedded tubes, especially for the case of the longitudinal extended surfaces.